Impacto energético e no solo decorrente do uso de biossólido industrial na produção de cana-de-açúcar e capim-elefante - Deus, Alex Santos de (2020)
The Biosolids are sludge from an effluent treatment plant, with a significant amount of organic matter and nutrients in its composition that make it usable in agriculture as a fertilizer. Studies prove the good results that this practice normally brings to the soil, the implanted culture and the economic viability of cultivation. The present study sought to understand the feasibility of the disposal of the biosolid produced by the effluent treatment station of a textile industry in the industrial pole of João Pessoa / PB in the soil, as a potential source of nutrients in the planting of sugarcane and grass. elephant. For this, an experiment was carried out on an experimental farm in the municipality of Pedras de Fogo-PB. The experimental design used was randomized blocks, composed of 6 (six) treatments: without fertilization, conventional fertilization, 1x, 2x, 4x and 8x the dose of biosolid recommended by CONAMA Resolution 375/06, with three repetitions each, totaling 18 (eighteen) experimental plots for each culture. In addition to the analyzes carried out directly with sugar cane and elephant grass, we also sought to understand the effects that biosolids can add to the soil, investigating possible physical-chemical losses or gains and possible contamination by heavy metals. The main expected result is to understand whether the use of biosolids as a fertilizer can replace commercial fertilizers, giving more environmental benefits, as well as good levels of productivity for sugar cane and elephant grass. It was also observed that the coefficient of variation (c.v.) of all variables involved in the analysis, for both sugarcane and elephant grass, was less than 20%, indicating good data homogeneity. From the results obtained over the total time of the experiment, approximately 02 years, it is observed that the biosolid was shown to be viable for application to the soil, provided that its dosage is made according to the dosage calculated by Conama Resolution 375/06.